2009
DOI: 10.1667/rr1545.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in Medical Workers Exposed to Radiation

Abstract: The use of nuclear resources for medical purposes causes considerable concern about occupational exposure. Nevertheless, little information is available regarding the effects of low-dose irradiations protracted over time. We used oligomicroarrays to identify the genes that are transcriptionally regulated by persistent exposure to extremely low doses of ionizing radiation in 28 exposed professionals (mean cumulative effective dose +/- SD, 19 +/- 38 mSv) compared with a matched sample of nonexposed subjects. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Radiation exposure, even at low dosage, has been shown to significantly affect levels of microRNAs in blood [63], [64], [65]. It is therefore possible that some of the changes in microRNA expression noted here are actually consequent to radiation exposure.…”
Section: Discussionmentioning
confidence: 83%
“…Radiation exposure, even at low dosage, has been shown to significantly affect levels of microRNAs in blood [63], [64], [65]. It is therefore possible that some of the changes in microRNA expression noted here are actually consequent to radiation exposure.…”
Section: Discussionmentioning
confidence: 83%
“…These genetic changes can be detected using transcriptomic technologies that permit thousands of genes to be analyzed in a single step to portray a genome-wide view of gene expression alterations. Few studies to date have used these technologies to identify transcriptomic signatures and genetic biomarkers related to IR exposure (Yin et al, 2003; Amundson et al, 2004; Dressman et al, 2007; Meadows et al, 2008, 2010; Lowe et al, 2009; Morandi et al, 2009; Kabacik et al, 2011; Wyrobek et al, 2011; Jaafar et al, 2013). These studies are starting to elucidate genetic targets associated with IR induced alterations, but were conducted in either cell culture systems, mature models, or from adult human peripheral blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term study of lymphocytes at 2, 7 and 55 days showed up to only five genes in common from the acute-to late-stage responses [41]. Different genes have also been shown to be up-regulated at low doses in comparison with high doses [42]. At low doses, a gender effect is also seen to influence the gene expression [40].…”
Section: Gene Expression Techniquesmentioning
confidence: 99%